2018
DOI: 10.1002/cncy.22069
|View full text |Cite
|
Sign up to set email alerts
|

Reducing DNA damage by formaldehyde in liquid‐based cytology preservation solutions to enable the molecular testing of lung cancer specimens

Abstract: Background Liquid‐based cytology (LBC) is a useful cytopathological method, and LBC lung adenocarcinoma specimens may be used for genetic analysis in the near future. In the current study, the authors determined whether LBC specimens can be used for epidermal growth factor receptor (EGFR) mutation analysis in human lung adenocarcinoma cell lines. Methods Genomic DNA was extracted from 3 lung adenocarcinoma cell lines that were fixed in LBC preservation solution using 2 protocols (one for cultured cells and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…This means that virtually any subsequent test can be performed on the material if it is stored correctly, from cytological (smears) to histological (cell blocks) preparations, with the whole array of ancillary tests at one’s disposal (immunocytochemistry, immunohistochemistry, flow cytometry, cytogenetics, molecular biology) [ 102 , 103 , 104 , 105 , 106 , 107 ]. One important factor that must not be overlooked in the context of molecular biology is that harvesting fresh (unfixed) material means that the quality of nucleic acids (both DNA and RNA) is at its best because no fixatives have been used and the risk of contamination is vastly reduced [ 108 , 109 , 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…This means that virtually any subsequent test can be performed on the material if it is stored correctly, from cytological (smears) to histological (cell blocks) preparations, with the whole array of ancillary tests at one’s disposal (immunocytochemistry, immunohistochemistry, flow cytometry, cytogenetics, molecular biology) [ 102 , 103 , 104 , 105 , 106 , 107 ]. One important factor that must not be overlooked in the context of molecular biology is that harvesting fresh (unfixed) material means that the quality of nucleic acids (both DNA and RNA) is at its best because no fixatives have been used and the risk of contamination is vastly reduced [ 108 , 109 , 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the Ct value and detection sensitivity of target genes for DNA and RNA were improved by devising means for extracting DNA and RNA. 28,29 The effect of formalin on the PCR method is not only the fragmentation of DNA and RNA, but also the cross-linking formation by formaldehyde. 30 The FFPE tissue samples are an important material used to archive the molecular analyses of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…When LBC specimens were fixed with CytoRich Red and DNA was extracted from the cells on glass slides, Kim et al similarly failed to detect BRAF exon 15 (a 226-bp PCR product) [25]. Another study reported poor or no detection of EGFR exon 19 (a 190-bp PCR product) from DNA extracted from cultured cells fixed in CytoRich Red fixative for more than 1 day [26]. The experimental protocol of this previous study was very similar to that of the present study, except that they used a higher cell density of 1 × 10 6 cells/mL for fixation.…”
Section: Discussionmentioning
confidence: 99%